Figural space semiotics and the aesthetic imaginary - Melaney, William D., 1953- (Global aesthetic research, 2021)
"This study provides a philosophical overview of select classics of Renaissance to contemporary literature to show how the notion of figural space is crucial to assessing the ethical and political aspects of literary study"--